Robustness analysis in forward modelling gravity data in crustal/lithospheric studies - POHÁNKA, Vladimír; VAJDA, Peter; BIELIK, Miroslav; DÉREROVÁ, Jana (Contributions to Geophysics and Geodesy, 2011)
The robustness of the gravimetric forward modelling is investigated by applying the harmonic inversion procedure at the input which is the difference of the calculated and measured surface gravity. The gravity data are taken from two profiles in the Carpathian-Pannonian Basin region. The result of the inversion are density models obtained from the original two-layer models with various horizontal boundary depth and density contrast. The deformation of the originally planar boundary is the measure of the mismatch between calculated and measured data. The calculated deformation has reached up to tens of kilometers and thus the uncertainties in determining the geometry of disturbing bodies by the forward modelling are substantial.